Are there literature reviews about gamification to foster Inclusive Teaching? A scoping review of gamification literature reviews - Ruiz-Navas, Santiago; Ackaradejraungsri, Pajaree; Dijk, Sandra (Frontiers in Education, 2024)
Introduction: Gamification can support the practical application of Inclusive Teaching. However, gamification literature reviews to implement Inclusive Teaching are scarce or not existent. Therefore, we conducted a scoping review of gamification literature reviews to identify what themes are covered and specifically if Inclusive Teaching has been explored. Method: The scoping literature review comprises network and content analyses of gamification literature reviews retrieved from the Web of Science. We analyzed a multimode network of papers and keywords and used their eigenvector centrality to identify themes. The content analysis comprised of a human and automatic tagging process to identify each paper's discipline/context. Results: We mapped the themes explored in 125 gamification literature reviews to answer our first research question, what are the areas of knowledge covered by gamification literature reviews? The central topic is gamification and education to increase motivation, followed by gamification itself and understanding the implementation of gamification in various contexts. We identified 12 contexts and the top five frequent were Education, Business, Gamification, and Political Science. From the year-byyear analysis, we separated the themes into four periods: beginning (2014)(2015), understanding (2016)(2017), focus 2018 and focus and emergence (2019)(2020)(2021)(2022). Regarding our second research question, how is the topic of Inclusive Teaching explored in gamification literature reviews? We did not find literature reviews about gamification to support Inclusive Teaching in the existing dataset. Discussion: We report on the benefits of organizing central keywords by quartiles and using multimode networks to support scoping reviews; and disadvantages and advantages of using literature reviews as data sources for scoping reviews. We invite researchers to create more gamification literature reviews, to investigate gamification ethics in the light of recent technological developments such as generative models, and to reconnect gamification to the game design elements part of its definition, which goes beyond game elements.